Philosophy in mass education system: Teaching as a mimetic practice - A. I. Pavlovskij (Russian State Vocational Pedagogical University, 2022)
Introduction. The article tackles the problem of changing the role and place of philosophy in the mass education system. Today, mass education is closely connected with pragmatisation and technologisation; and these two processes spawn a concern whether it is useful to study philosophy, and, as a consequence, an aspiration to transform the understanding of teaching itself.Aim. The aim of the present paper was to reconceptualise the bespoke teaching experience within the framework of personalised academic tracks launched in the University of Tyumen in an attempt to address the problem.Methodology and research methods. The theoretical part of the research lays out the foundation of philosophy teaching as a mimetic practice based on a methodology, which is developed through the following concepts: the dichotomy of E. Giddens' practical and discursive consciousness, M. Polanyi's tacit knowledge, E. Mach's economy of thought, and C. Wulf's mimesis. This was a starting point of a philosophy teaching practice that was tested on a batch of students, approximately a quarter of which agreed to take an anonymous survey about the process and the results of the joined work.Results and scientific novelty. A draft of a conceptual foundation of mass philosophy teaching in the current context is laid out. At the core of the process, there is a mimetic transfer of tacit knowledge, ensuring a skill to philosophise. This process presupposes an interaction of four actors: a teacher, a student, a text and a group of students. The lecture is a demonstration of a personal philosophic style, and the Socratic seminar is a joint practice with an unpredictable finale. In this practice, there is a system, where the teacher is an inquiring moderator launching the student's personal search, the text provides a connection with a philosophic tradition, and the group - with the everyday life. The survey showed that this approach is effective: students like the process, they understand the connection of the philosophical ideas with the real life, and they track the level of their own understanding of philosophical texts.Practical significance. The research results may be useful for other philosophy teachers who on the basis of this study may adjust their teaching practices to a mass philosophy course delivered in the current conditions; and for further development of the theory, first and foremost, in terms of formulating the philosophical content being used.